RANCANG BANGUN WEBSITE SISTEM ADMINISTRASI PEMBAYARAN SPP DAN PENDAFTARAN SISWA BARU - Yuntari ZB; Nur Aini H; Ariansyah (JURNAL ILMIAH BETRIK : Besemah Teknologi Informasi dan Komputer, 2022)
Al-Munawwarah Prabumulih is engaged in Kindergarten (TK) education, this school often has problems with recording new student admissions and making reports that still use the manual system, the problem is that there is no adequate system to overcome this . And student financial payments are still less effective and less efficient where in recording, especially in tuition payments, it is done repeatedly, causing a long process in processing data and can spend time especially when going to recap payments or reports made monthly. and annually, with manual recording using handwriting, the possibility of data and documents being lost or damaged is very large, besides that the new student admission system still uses a manual system which often causes ineffective recording problems. So it is necessary to build a system that makes it easier to input and store new student data, make it easier to make new student admission announcements, make it easier to make new student admission reports quickly and accurately. And tuition payments to facilitate the process of student tuition payment transactions, facilitate the manufacture of student tuition payment reports on a monthly basis, facilitate the preparation of reports for students who have not paid arrears. The design of this information system uses the prototype method, using the PHP and MySql programming languages. The design method used in this research uses the UML (Unifield Modeling Language) design method using 3 diagrams, namely Use Case Diagrams, Activity Diagrams, and Class Diagrams. The website-based information system at RA Al-Munawwarah Prabumulih will make it easier and provide an efficient and effective aspect for prospective new students to register and RA Al-Munawwarah Prabumulih students make tuition payments.